Hubungan Lama Penggunaan Gawai Terhadap Kualitas Tidur Siswa SMAN 112 Jakarta Semester Genap Tahun Akademik 2022 2023 - Mufida, Farah Dwi Rizardina; Hartono, Budiman; Wijaya, Diana (Jurnal MedScientiae, 2025)
The use of gadgets in teenagers can’t be separated from the demands of education and entertainment, making teenagers the age group with the highest use of gadgets. Gadgets are also a risk factor that can affect sleep quality. Emission of blue light can disrupt the regulation of the work of the hormone melatonin in the human body, which plays an important role in the regulation and quality of human sleep. This study aims to determine the relationship between the duration of device use and sleep quality in adolescents. The analysis which used in this study is the Pittsburgh Sleep Quality Index (PSQI) questionnaire with data on the number of students who had poor sleep quality as many as 105 students (67.74%) and good sleep quality as many as 50 students (32.26%). The results of the cross table show data that students who have poor sleep quality with high duration of device use are 93 respondents (60%). Chi-Square analysis shows the p-value is 0.000 (p <0.05). So it can be concluded that there is a relationship between the length of use of devices and the quality of sleep among students at SMAN 112 Jakarta, Academic Year 2022 2023.